Existence and Multiplicity of Positive Solutions for a Singular Nonlinear High Order Fractional Differential Problem with Multi-Point Boundary Conditions (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, a singular nonlinear high order fractional differentialproblem involving multi-point boundary conditions is solved by means of thefixed point index theory. Some properties of the first eigenvalue correspondingto relevant operator and some new height functions are also used to prove theexistence and multiplicity of positive solutions. The nonlinearity depends onarbitrary fractional derivative.